1979
DOI: 10.1128/jvi.32.1.251-258.1979
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Maturation of Mouse Mammary Tumor Virus Precursor Polypeptides in Lymphoid Leukemia Cells, Producing Intracytoplasmic A Particles and No Extracellular B-Type Virions

Abstract: Processing of polypeptides of the mouse mammary tumor virus, a type B retrovirus, was investigated in a transplanted thymic lymphoma cell line of the GR strain (GRSL). This cell line was maintained in vivo in ascites form and in vitro as a suspension culture. GRSL cells produce clusters of intracytoplasmic A particles and are virtually deficient in the production of mature extracellular Btype particles. As control, a mammary tumor cell line of the same mouse strain capable of complete virion synthesis was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…It had previously been reported that a T-cell lymphoma line was not able to process virus proteins and therefore could not produce infectious virus particles (16). To determine if all of the cells were able to produce MMTV proteins, Western blot analysis was performed on total cell extracts with monospecific anti-SU ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It had previously been reported that a T-cell lymphoma line was not able to process virus proteins and therefore could not produce infectious virus particles (16). To determine if all of the cells were able to produce MMTV proteins, Western blot analysis was performed on total cell extracts with monospecific anti-SU ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4). Thus, there is no general block to the production of infectious MMTV virions in B-or T-cell tumor lines, although some cell lines may not process the viral proteins (16).…”
Section: Resultsmentioning
confidence: 99%
“…Mouse mammary tumor virus (MMTV), the causative agent of mammary tumors in susceptible mice, is also known to be expressed in tissues and tumors other than those of the mammary gland. The most extensively documented association of MMTV with nonmammary tumors is that with T-cell lymphomas (1,8,22,27,32). A characteristic common to all the MMTV-expressing T-cell lymphomas is the presence of numerous acquired (amplified) MMTV proviral genomes (8,22), all containing long deletions in their long terminal repeat (LTR) regions (1,14,17,18,21,23).…”
mentioning
confidence: 99%
“…Transcription assay constructs containing MMTV LTRs bearing deletions appear to be more efficient in lymphoid cells than constructs with full-length LTRs (35). The T-cell lymphoma cells do not produce mature viral particles (27,32), although they do transcribe high levels of MMTV RNA (9,17,23,30). The mRNAs are translated into gag and env polyprotein precursors but are then not processed further into mature viral structural proteins because of an apparent block in the maturation pathway (27,32).…”
mentioning
confidence: 99%
See 1 more Smart Citation